Valorization of Aromatic Hydrocarbons into Polyhydroxyalkanoates: Advances Towards Sustainable Waste Gas Treatment - Poblete-Castro, I (Elsevier Ltd, 2025)
Benzene, toluene, ethylbenzene, xylene and styrene (BTEXS) are priority gaseous pollutants due to their widespread release and health risks. This study demonstrates an efficient BTEXS bioconversion process into polyhydroxyalkanoates (PHA) using a specialized mixed microbial culture dominated by Pseudonocardia and Rhodococcus. The consortium achieved simultaneous degradation rates of 15.1 ± 3.9 g m−3h−1 for toluene and 17.6 ± 5.7 g m−3h−1 for ethylbenzene, with removal efficiencies over 90 %. The operating strategy promoted PHA accumulation up to 21.4 % gPHA gDCW−1. A two-step process was successfully implemented consisting of an initial reactor for biomass growth followed by a second reactor under nitrogen deprivation. PHA analysis revealed the synthesis of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) copolymer with a dynamic increase in 3-hydroxyvalerate content under prolonged nitrogen starvation. Metagenomics provided insights into the microbial networks and metabolic pathways involved in the process. This research offers a sustainable solution for mitigating BTEXS pollution while producing valuable bioplastics. © 2025 The Author(s)